Getting in shape with minimal energy: a variational principle for protohaloes. Issue 1 (6th April 2023) - Musso, Marcello; Sheth, Ravi K
ABSTRACT: In analytical models of structure formation, protohaloes are routinely assumed to be peaks of the smoothed initial density field, with the smoothing filter being spherically symmetric. This works reasonably well to identify a protohalo's centre of mass, but not its shape. To provide a more realistic description of protohalo boundaries, one must go beyond the spherical picture. We suggest that this can be done by looking for regions of fixed volume, but arbitrary shape, that minimize the enclosed energy. Such regions are delimited by surfaces over which (a slightly modified version of) the gravitational potential is constant. We show that these equipotential surfaces provide an excellent description of protohalo shapes, orientations, and associated torques.